Quantification methods for carbohydrate compounds in biologicals: a review - A. S. Minero; O. B. Rounova; O. B. Ustinnikova (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Carbohydrate compounds are widely used as fillers and stabilisers in biological products. When present, these compounds guarantee that the active pharmaceutical ingredient will remain stable during production, transportation, and storage. At the same time, pharmacopoeias standardise the excipient content and require that excipients should be quantified for assessing the quality of biological products.The aim of the study was to identify promising methods for the development of quantification procedures for carbohydrate compounds in biological products.The authors analysed regulatory documents for biological products approved in the Russian Federation. The most widely used excipients, both individually and in combinations, are polyols (sorbitol and mannitol), monosaccarides (glucose), and disaccharides (trehalose, sucrose, lactose, and maltose). Using literature data, the authors reviewed the methods used for quantifying polyols, monosaccharides, and disaccharides to assess the quality of biological products. Quantitative determination of carbohydrate stabilisers employs titrimetric, spectrophotometric, enzymatic, and chromatographic methods. This review presents an analysis of the advantages and disadvantages of these methods. It highlights the advantages of ionic HPLC with amperometric detection and hydrophilic HPLC with refractometric and evaporative light scattering detection, which are sufficiently selective and can identify substances without prior derivatisation. In conclusion, ionic and hydrophilic HPLC methods are a promising base for the development of quantification procedures for carbohydrate stabilisers.